Postsurgical stability of counterclockwise maxillomandibular advancement surgery: Affect of articular disc repositioning - Gonçalves, João Roberto [UNESP]; Cassano, Daniel Serra; Wolford, Larry M.; Santos-Pinto, Ary [UNESP]; Marquez, Iris Malagoni (W B Saunders Co-elsevier Inc, 2008)
Purpose: This study evaluated the affect of disc displacement and articular disc repositioning on stability after surgical counterclockwise rotation and advancement of the maxillomandibular complex.Patients and Methods: A total of 72 patients (59 females, 13 males), with an average age of 30 years (range, 15 to 60 years) were evaluated. The patients were divided into 3 groups. Group 1 (G1; n = 21), with healthy temporomandibular joints (TMJs), underwent double jaw surgery only. Group 2 (G2; n = 35), with articular disc dislocation, underwent articular disc repositioning using the Mitek anchor (Mitek Surgical Products, Westwood, MA) technique concomitantly with orthognathic surgery. Group 3 (G3; n = 16), with articular disc dislocation, underwent orthognathic surgery only. Average postsurgical follow-up was 31 months. Each patient's lateral cephalograms were traced, digitized twice, and averaged to estimate surgical changes and postsurgical stability.Results: After surgery, the occlusal plane angle was decreased significantly in all 3 groups: by -6.3 +/- -15.0 degrees in G1, by -9.6 +/- 4.8 degrees in G2, and by -7.1 +/- 4.8 degrees in G3. The maxillomandibular complex was advanced and rotated counterclockwise similarly in all 3 groups, with advancement at the menton of 12.4 +/- 5.5 mm in G1, 13.5 +/- 4.3 mm in G2, and 13.6 +/- 5.0 mm in G3; advancement at the B point of 9.5 +/- 4.9 mm in G1, 10.2 +/- 3.7 mm in G2, and 10.8 +/- 3.7 mm in G3; and advancement at the lower incisor edge of 7.1 +/- 4.6 mm in G1, 6.6 +/- 3.2 mm in G2, and 7.9 +/- 3.0 mm in G3. Postsurgery, the occlusal plane angle increased in G3 (2.6 +/- 3.8 degrees; 37% relapse rate) but remained stable in G1 and G2. Postsurgical mandibular changes in the horizontal direction demonstrated a significant relapse in G3 at the menton (-3.8 +/- 4.1 mm; 28%), the B point (-3.0 +/- 3.4 mm; 28%), and the lower incisor edge (-2.3 +/- 2.1 mm; 34%) but remained stable in G1 and G2.Conclusions: Maxillomandibular advancement with counterclockwise rotation of the occlusal plane is a stable procedure for patients with healthy TMJs and for patients undergoing simultaneous TMJ disc repositioning using the Mitek anchor technique. Those patients with preoperative TMJ articular disc displacement who underwent double-jaw surgery and no TMJ intervention experienced significant relapse. (C) 2008 American Association of Oral and Maxillofacial Surgeons.